Digital Literacy Skills: A Sine Qua Non for Effective Teaching Practice Supervision of Mathematics Education Pre-service Teachers in an Open Distance and e-Learning Environment - Age, Terungwa James; MACHABA, Masilo France (Universitas Islam Negeri Raden Intan Lampung, 2026)
The rapid expansion of digital learning environments in mathematics education has revealed fundamental limitations in how teaching practice supervision is conceptualized and implemented, particularly within Open Distance and e-Learning (ODeL) contexts where conventional supervisory models are increasingly inadequate. This study critically examines the role of digital literacy in shaping supervision practices and advances an integrated conceptual framework that links digital competencies with supervisory processes. A systematic literature review was conducted through a structured selection of ten studies, enabling a rigorous thematic synthesis of recurring patterns and relationships. The findings demonstrate that digital literacy operates as a multidimensional construct encompassing technical, pedagogical, communicative, and assessment-related competencies that collectively redefine how supervision is enacted in digitally mediated learning environments. The analysis further reveals that the effectiveness of digital literacy is inherently conditional, shaped by the interplay of infrastructure, institutional support, and professional training, thereby challenging assumptions that technological adoption alone enhances supervision quality. In addition, the study exposes a persistent fragmentation in the literature, where digital literacy and supervision are often treated as disconnected domains. Addressing this gap, this study advances a systemic and interactional framework that captures the dynamic relationships between digital literacy, supervision practices, and contextual conditions. This framework not only contributes to theoretical refinement but also provides a robust foundation for rethinking supervision in mathematics education within increasingly digitalized learning systems.